Pelatihan Kewirausahaan Non-Digital (SMESKA) Untuk UMKM Di Surakarta Oleh UPTD KST Solo Technopark - Shofiyana Futri; Mei Retno Adiwaty (Universitas Katolik Widya Karya Malang, 2023)
In this era of globalization and rapidly advancing technology, the level of competition in finding work and income is getting higher. This is due to a mismatch between the number of jobs available and the number of job seekers. Therefore, we cannot continue to depend on existing job vacancies, but there should be a desire within us to be self-employed. In addition, not all of the existing Micro, Small and Medium Enterprises (MSMEs) have produced the desired output. One of the big challenges for SMEs is the lack of entrepreneurial knowledge and skills needed to manage the business effectively. It is necessary to strive for training that can provide the necessary knowledge, skills and resources to MSME owners so that they can optimize their business potential. This entrepreneurship training method uses two methods, namely training by providing material as well as discussion and question and answer. From the results of the implementation of this training program, the participants' responses were enthusiastic and positive. It can be seen from the enthusiasm of the participants which is reflected in their active participation in the training. The participants also demonstrated their understanding of entrepreneurship which was strengthened by their ability to answer the mentor's questions.